Optimization of thermal management and power density of small-scale wind turbine applications using SiC-MOSFETs - Hussein, Abdallah; Castellazzi, Alberto (2017)
This paper presents an optimized design of 12kW 2L-FB inverter for small-scale wind turbine, taking into account some specific behavioral features of SiC power MOSFETs. Power converters used in renewable energy conversion have to deal with intermittent and variable power availability from the source, which implies that they actually work at their maximum rated power for only a small fraction of their operational time. Still, traditional thermal management design of power modules has to refer to maximum load conditions. SiC-MOSFETs exhibit a very stable performance over a broad temperature range [1-3]; this feature enables to design the cooling device for nominal operational conditions, typically corresponding to a much lower than maximum power rating. When this capability is added to the decrease in the size of passive filter elements, which can be gained by the higher switching frequency capability of SiC MOSFETs, the result is a significant increase of the converter powe, density.